2003
DOI: 10.1111/j.1945-5100.2003.tb00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of sulfur on the surface of asteroids and the moon

Abstract: The bulk composition appears to be consistent with that of L to H chondrites (Nittler et al. 2001). However, there appeared to be a marked depletion relative to ordinary chondritic composition in the S/Si ratio (0.014 ± 0.017). We investigate space weathering mechanisms to determine the extent to which sulfur can be preferentially lost from the surface regolith. The two processes considered are impact vaporization by the interplanetary meteoroid population and ion sputtering by the solar wind. Using impact dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Sasaki et al (2006) have suggested that the resurfacing process on Itokawa may be caused by seismic destruction due to impacts or tidal stress as a result of planet encounters, and thus the portion of exposed material on the surface may be little altered materials by space weathering. Killen (2003) and Kracher and Sears (2005) have suggested that it is easy to remove the sulfur on the asteroid surface by space weathering in the uppermost layer of 10-100 μm per 10 6 years, and thus the sulfur abundance on the surface may vary between little and highly altered areas. Since our result did not indicate a global depletion of sulfur, in spite of large errors, the abundance of sulfur may be fresh in local areas due to the resurfacing process compared to highly altered materials by space weathering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sasaki et al (2006) have suggested that the resurfacing process on Itokawa may be caused by seismic destruction due to impacts or tidal stress as a result of planet encounters, and thus the portion of exposed material on the surface may be little altered materials by space weathering. Killen (2003) and Kracher and Sears (2005) have suggested that it is easy to remove the sulfur on the asteroid surface by space weathering in the uppermost layer of 10-100 μm per 10 6 years, and thus the sulfur abundance on the surface may vary between little and highly altered areas. Since our result did not indicate a global depletion of sulfur, in spite of large errors, the abundance of sulfur may be fresh in local areas due to the resurfacing process compared to highly altered materials by space weathering.…”
Section: Discussionmentioning
confidence: 99%
“…Nittler et al (2001) suggested that the reason for low S/Si is impact-induced volatilization and/or photoor ion-induced sputtering at the surface of the asteroid, or the loss of FeS-rich material due to partial melting. Also, a sulfur volatilization process due to space weathering, such as micro-meteorite impacts or/and energetic erosion due to solar wind sputtering, has been proposed by Killen (2003) and Kracher and Sears (2005). Their timescale estimation for sulfur depletion in the uppermost layer of 10-100 μm due to space weathering is the order of 10 6 years, so that sulfur on the surface can easily be taken away from the uppermost layer.…”
Section: Introductionmentioning
confidence: 99%
“…The processes hypothesized to destroy sulfides on Eros are much more vigorous on Mercury. Mean micrometeoroid impact velocities are much greater at Mercury (~20 km/s) [ Cintala , ] than at the location of Eros (~9 km/s) [ Killen , ]. The flux of micrometeoroids is also greater at Mercury.…”
Section: Formation Hypothesesmentioning
confidence: 99%
“…This model for impact vaporization is based on the impedance matching method [ Melosh , 1989; Morgan and Killen , 1998; Killen , 2003] and the total influx is an input parameter.…”
Section: Lunar Atmospheric Modelmentioning
confidence: 99%